IgG4-Related Disease: Comprehensive Overview of Pathogenesis, Clinical Manifestations, and Diagnostic Challenges. - Bartoszek, Lidia; Orłowska, Dominika; Olszak, Joanna; Zalewa, Karolina; Kapłan, Wojciech; Starownik, Jakub; Gastoł, Bartłomiej (Quality in Sport, 2024)
Introduction IgG4-related disease (IgG4-RD) is a progressive and potentially life-threatening condition characterized by immune system activation and tissue fibrosis, affecting various organs such as the pancreas, kidneys, and lungs. Initially recognized in 2003, it often presents as mass-like lesions, which can mimic tumors. Despite advancements in understanding its pathology, epidemiological data are limited, and many patients remain undiagnosed due to unfamiliarity with the disease. Aim of the study The aim of this article wast to summarize the latest knowledge on the diagnosis and clinical manifestations of IgG4-related disease. Materiał and methods This review is based on articles from the PubMed and Google Scholar databases, covering the years 2007-2024, using the keywords: IgG4-related disease; autoimmune pancreatitis; retroperitoneal fibrosis; classification criteria. Results The disease’s complex pathogenesis involves B and T cell activity, with genetic and environmental factors contributing. While effective treatments, like B cell depletion, exist, the disease’s broad clinical manifestations and multi-organ involvement require a multidisciplinary approach for proper diagnosis and management. Conclusion Diagnosing IgG4-RD is challenging due to its varied symptoms, often mimicking other diseases. Key findings include high IgG4 levels and specific histopathological features. Further research is needed to understand its genetic factors, pathogenesis, and epidemiology.